1998
DOI: 10.1021/jp972546m
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study of Chromium Oxide Clusters:  Structures, Bonding, Vibrations, and Stability

Abstract: We report the results of density functional theory calculations on chromium oxide clusters responding to the formula Cr m O n (m ) 1-2, n ) 1-3). Double numeric basis sets supplemented by polarization functions have been used in both local and nonlocal spin density approximations. Geometry optimizations of different spin states have been performed at the unrestricted spin level for the selected initial configurations. We have found that the covalent polarized Cr-O bonds dominate the chemical description of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 29 publications
7
80
3
Order By: Relevance
“…The value of 1.6×10 -10 m comes from a density functional theory estimation of the length of a Cr-O bond in CrO. 11 The values of v i for the mixtures other than air were based on a weighted average of the component v i values.…”
Section: Diffusion Coefficient D Abmentioning
confidence: 99%
“…The value of 1.6×10 -10 m comes from a density functional theory estimation of the length of a Cr-O bond in CrO. 11 The values of v i for the mixtures other than air were based on a weighted average of the component v i values.…”
Section: Diffusion Coefficient D Abmentioning
confidence: 99%
“…In their theoretical calculation of chromium oxide clusters, Veliah et al 41 found that CrO n -type clusters are more stable than Cr m O n -type clusters. The CrO n -type clusters presented Cr O bonds with covalent and polar features.…”
Section: Segregated And/or Precipitated Chromium Dopant and The Nonohmentioning
confidence: 99%
“…Chromium oxide clusters, both neutral and anionic, have been a topic of current research interest [8][9][10][11][12][13][14]. Different properties of neutral chromium oxide clusters have been correlated with electronic structure by Pandey and coworkers [8].…”
Section: Introductionmentioning
confidence: 99%
“…Different properties of neutral chromium oxide clusters have been correlated with electronic structure by Pandey and coworkers [8]. Whereas, the variation of their electronic structure as well as the magnetic property as a function of oxidation and composition have been discussed by Zhai and Wang [9] and Reddy and Khanna [10], respectively.…”
Section: Introductionmentioning
confidence: 99%